An Analysis of Branding at Islamic Universities Using Mark and Pearson’s Archetypes - Nur Asiyah; Robith Khoiril Umam; Yustin Sartika (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
Competition between universities to gain market attention requires various strategies, including the activities of the institution's branding. University branding is obligatory to publicize their existence and values, which differ from competitors, whether in scientific values or other elements. However, sometimes stakeholders to not understand the